Biology in the 21st-Century: Transformation in biology science and education in supporting the sustainable development goals - Wibowo, Yudha Gusti; Sadikin, Ali (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
The transformation in education must be directed in accordance with Sustainable Development Goals (SDGs) program. This article aimed to discuss the potential support of New Biology in achieving the formulated SDGs. This literature review covered 31 articles which were published since 2010 to 2019. The keywords used to collect the data were new biology, future biology, biology education, biological science, and biology. The review results informed that New Biology can potentially enact five goals of SDGs, i.e. goal 2 (Zero Hunger), goal 3 (Good Health and Well-being), goal 4 (Quality Education), goal 6 (Clean Water and Sanitation), and goal 7 (Affordable and Clean Energy). By considering the findings, it is suggested to promote New Biology approach in Indonesian educational system.